Introduction to Curriculum for Early Childhood Education - Paris, Jennifer; Beeve, Kristin; Springer, Clint (Open textbook library., 2019)
Welcome to learning about how to effectively plan curriculum for young children. This textbook will address: Developing curriculum through the planning cycle Theories that inform what we know about how children learn and the best ways for teachers to support learning The three components of developmentally appropriate practice Importance and value of play and intentional teaching Different models of curriculum Process of lesson planning (documenting planned experiences for children) Physical, temporal, and social environments that set the stage for children’s learning Appropriate guidance techniques to support children’s behaviors as the self-regulation abilities mature. Planning for preschool-aged children in specific domains including Physical development Language and literacy Math Science Creative (the visual and performing arts) Diversity (social science and history) Health and safety How curriculum planning for infants and toddlers is different from planning for older children Supporting school-aged children’s learning and development in out-of-school time through curriculum planning Making children’s learning visible through documentation and assessment